2020
DOI: 10.1002/jmri.27342
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Vascular Reactivity of Maternal Vascular Adaptations of Pregnancy With Quantitative MRI: Pilot Study

Abstract: BackgroundAbnormal maternal vascular function during pregnancy stemming from systemic endothelial dysfunction (EDF) has a central role in the pathophysiology of preeclampsia (PE).PurposeTo utilize quantitative MRI to investigate changes in physiological measures of vascular reactivity during normal pregnancy, and to explore EDF associated with preeclampsia.Study TypeProspective.PopulationHealthy pregnant (HP) (n = 14, mean GA = 26 ± 7 weeks) and nonpregnant women (NP; n = 14); newly postpartum (PP <48 hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Our ability to treat preeclampsia and other gestational hypertensive disorders depends on a better understanding of normal and abnormal vascular adaptations during pregnancy. The current study by Langham et al 6 clearly demonstrated the feasibility of comprehensive assessments of microvascular and macrovascular functions, and aortic stiffness of the aorta by MRI, and appears to be an important step in this direction.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…Our ability to treat preeclampsia and other gestational hypertensive disorders depends on a better understanding of normal and abnormal vascular adaptations during pregnancy. The current study by Langham et al 6 clearly demonstrated the feasibility of comprehensive assessments of microvascular and macrovascular functions, and aortic stiffness of the aorta by MRI, and appears to be an important step in this direction.…”
mentioning
confidence: 51%
“…In this issue of JMRI, Langham et al evaluated the altered systemic endothelial function in pregnant women and nonpregnant women with magnetic resonance imaging (MRI), by inducing reactive hyperemia in the superficial femoral arteries and veins via cuff‐induced ischemia 6 . Microvascular function was assessed by monitoring oxygen saturation (SvO 2 ) of venous blood in the femoral veins by using dynamic MR oximetry.…”
mentioning
confidence: 99%
“…Different cells achieve intercellular communication by secreting exosomes carrying different components. Exosomes are closely related to the occurrence and development of some diseases, and previous studies have shown that exosomes play a role in immune response, inflammation, tumor, angiogenesis and other processes [12] . Human reproduction, pregnancy, and embryonic development require dynamic intercellular communication, and exosome-mediated intercellular communication begins before implantation.…”
Section: Overview Of Exosomesmentioning
confidence: 99%